An odontoma causing a delay in teeth eruption in an 11-year old boy. Case report - Ewelina Bracik; Karolina Buczyńska; Tomasz Krzysztof Bąk; Anna Gawęda; Jolanta Wojciechowicz; Tomasz Tomaszewski (Kazimierz Wielki University, 2018)
Odontomas are the benign tumors, which are usually discovered by chance in radiographic images taken because of anomalies such as delayed eruption of teeth or malocclusion. Case study shows the course of diagnosis of an asymptomatic odontoma  in youth, followed by a failure in teeth development.